Preparation method of porous geopolymer-supported zinc ferrite desulfurizer
By foaming pores in the geopolymer carrier, a porous geopolymer-loaded zinc ferrite desulfurizer is formed, which solves the problem that H2S gas is difficult to effectively remove in the IGCC system, and achieves an efficient and low-cost desulfurization effect.
Patent Information
- Application Number
- CN202410413844.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-08
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-04-08
AI Technical Summary
In the IGCC system, high-temperature coal gas contains a large amount of H2S gas, resulting in equipment corrosion, catalyst poisoning and environmental pollution. The existing metal oxide desulfurizers have their own advantages and disadvantages, and it is difficult to meet the requirements of efficient desulfurization and low cost at the same time.
Pore formation is formed by foaming pores in the geopolymer carrier to form a porous geopolymer-loaded zinc ferrite desulfurization agent, so that the zinc ferrite particles are evenly distributed and adsorption is enhanced, and the retention time of H2S gas is extended, thereby improving the desulfurization effect.
The desulfurization effect of zinc ferrite particles is significantly improved, the adsorption property and retention time are enhanced, and the desulfurization efficiency and cost problems in the prior art are solved.
Smart Images

Figure CN118109230B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of desulfurizing agents, and in particular to a method for preparing a porous geopolymer-loaded zinc ferrite desulfurizing agent. Background Art
[0002] At present, my country's energy still mainly relies on coal resources, and the consumption of coal resources accounts for about two-thirds of the total resource consumption, and about half of it is used for power generation. Integrated gasification combined cycle power generation (IGCC) technology is currently considered to be the most promising power generation technology. However, the high-temperature coal gas produced in the IGCC system contains a large amount of sulfur-containing gas, 90% of which is H2S. These gases will not only corrode equipment and poison catalysts, but also cause serious environmental pollution and endanger people's physical and mental health. Therefore, removing H2S before using high-temperature coal gas is an essential key step.
[0003] Most metal oxides can be used as high-temperature coal gas desulfurizers, but each metal oxide has its own advantages and disadvantages as a desulfurizer, for example: Fe2O3 has a fast sulfidation rate and is easy to regenerate; ZnO has high desulfurization accuracy; CaO has good desulfurization performance, is cheap and easy to obtain; copper oxide has a high desulfurization efficiency as a high-temperature coal gas desulfurizer and is easy to regenerate, but CuO is easily reduced to Cu elemental and sintered at high temperatures; CeO2's product Ce2O2S after sulfidation can directly generate elemental S by reacting with SO2. In recent years, in order to improve the desulfurization performance of metal oxides, the research focus has shifted from single metal oxides to composite metal oxides. Zinc ferrite desulfurizer, as a composite metal oxide desulfurizer, has attracted domestic and foreign attention because it has the characteristics of fast reaction rate and high sulfur capacity of Fe2O3 and high desulfurization accuracy and low preparation cost of ZnO, and has good desulfurization effect. Various patents on zinc ferrite desulfurizers have emerged in an endless stream, among which the Chinese patent document CN101440313A discloses a medium, The invention discloses a high-gas anti-pulverization zinc ferrite desulfurizer and a preparation method thereof. The invention mainly comprises the following steps: coprecipitating zinc nitrate and zinc ferrite in an ammonia environment system with a pH value of 9-10 to prepare active zinc ferrite; and then roasting the active zinc ferrite at 600-800°C with 15-30wt% clay as a carrier and 6-12wt% pore-forming agent as an auxiliary agent to prepare the desulfurizer; wherein the auxiliary agent has a bonding effect, uniformly dispersing zinc ferrite particles, avoiding agglomeration of zinc ferrite particles, increasing specific surface area, and being beneficial to improving desulfurization efficiency and sulfur capacity.
[0004] Geopolymer, also known as geopolymer in English, was proposed and studied by Davidovits of France in 1978. It is a new type of inorganic polymer gel material with a three-dimensional spatial network structure obtained by activating active raw materials rich in silicon and aluminum, such as metakaolin, fly ash, slag, tailings, etc., by alkaline activators (mixed solutions of sodium hydroxide, potassium hydroxide, sodium silicate, and potassium silicate). The hydration reaction of geopolymer is completely different from that of silicate cement. It is an inorganic polymerization reaction. Its preparation does not require the high temperature of silicate cement, and its energy consumption is much lower than that of silicate cement. It does not emit so much harmful gas and dust during the production process, and there is almost no CO2 emission, almost no environmental pollution. Moreover, this gel not only has excellent mechanical properties, but also has stronger acid and alkali resistance, high temperature resistance, and fire resistance than silicate cement.
[0005] Geopolymer also has a porous structure similar to zeolite, and can effectively adsorb and disperse zinc ferrite desulfurizer as a carrier of zinc ferrite desulfurizer. Moreover, the preparation process of geopolymer is simple, and the equipment is single. Due to its own viscosity and strength, zinc ferrite can be firmly fixed inside the geopolymer carrier without high-temperature roasting. Because it is synthesized under a strong alkaline environment and has a porous structure inside, studies have shown that geopolymer has a large pore content and strong adsorption. Based on these characteristics, geopolymer itself is very likely to have a certain desulfurization effect. Therefore, the present invention further foams and pores the geopolymer to strengthen its pore structure, so that the zinc ferrite particles are more evenly distributed inside the geopolymer carrier, and at the same time, its adsorption is enhanced by pore formation, so that the H2S gas retention time is prolonged. All of the above can promote the desulfurization effect of zinc ferrite particles. Summary of the invention
[0006] The present invention aims to provide a method for preparing a porous geopolymer-loaded zinc ferrite desulfurizer, by further foaming and pore-forming the geopolymer to strengthen its pore structure, so that the zinc ferrite particles are more evenly distributed inside the geopolymer carrier, and at the same time, the adsorption is enhanced by pore-forming to prolong the retention time of H2S gas, thereby improving the desulfurization effect of the zinc ferrite particles.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a porous geopolymer-supported zinc ferrite desulfurizer comprises the following steps:
[0009] S1. Preparation of NaOH solution
[0010] Weigh an appropriate amount of granular or flake NaOH and pour it into water, stir until completely dissolved to prepare a NaOH strong alkaline solution, seal it and let it stand and cool for 24 hours, then bottle it for later use;
[0011] S2. Adjust the water glass modulus
[0012] Weigh an appropriate amount of the NaOH strong base solution in step S1, pour it into a commercially available sodium water glass solution, let it stand and cool to room temperature to obtain the prepared water glass solution, and bottle it for later use;
[0013] S3, dry mixed solid particle powder material
[0014] Weigh appropriate amounts of metakaolin, zinc ferrite or fly ash, zinc ferrite, pour the two substances into a mixer and dry mix them, mix thoroughly to obtain a mixed dry material, and set aside for later use;
[0015] S4. Preparation of semi-finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0016] Weigh an appropriate amount of aluminum powder or zinc powder and add it to the prepared water glass solution in step S2, stir it with a glass rod for 3-5 minutes, let it stand for 3-5 minutes, pour it into a mixer and stir it with the mixed dry material in step S3 for 6-10 minutes, and finally obtain a geopolymer carrier in the form of a zinc ferrite-loaded desulfurizer semi-finished slurry, let it stand for foaming and then set aside;
[0017] S5. Preparation of finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0018] The semi-finished slurry in step S4 is poured into a mold of a certain size, and placed in a programmable constant temperature and humidity test box for curing for 3-6 hours. Finally, the cured sample is crushed to obtain a finished product of a small-particle porous geopolymer-loaded zinc ferrite desulfurizer.
[0019] Preferably, the water in step S1 is deionized water, the purity of the granular or flaky NaOH is ≥96%, and the concentration of the NaOH strong alkaline solution is 8-12 mol / L.
[0020] Preferably, the water glass modulus of the prepared water glass solution in step S2 is between 1.2 and 2.0; the water glass modulus of the commercially available sodium water glass solution is 3.25, and the water content is 64.18%.
[0021] Preferably, in step S3, the mass ratio of metakaolin:zinc ferrite or fly ash:zinc ferrite is 0.2-1.0:1.
[0022] Preferably, the mixer in step S3 and step S4 is a planetary mixer, and the dry mixing in step S3 specifically refers to low-speed mixing at a rotation speed of 120-180 r / min for 5-10 minutes.
[0023] Preferably, the mass of the aluminum powder or zinc powder in step S4 accounts for 0.5-1.0wt% of the mixed dry material in step S3.
[0024] Preferably, the stirring for 6-10 minutes in step S4 specifically refers to first stirring at a low speed of 120-180 r / min for 3-5 minutes, and then stirring at a high speed of 200-300 r / min for 3-5 minutes.
[0025] Preferably, the water-to-binder ratio of the geopolymer carrier in step S4 is 0.38-0.5.
[0026] Preferably, the foaming time in step S4 is not less than 90 minutes.
[0027] Preferably, the curing temperature of the programmable constant temperature and humidity test box in step S5 is 40-80° C., and the humidity is 50-80%.
[0028] In summary, the present invention has the following beneficial effects:
[0029] Compared with the prior art, the preparation method provided by the present invention can strengthen the pore structure of the geopolymer through foaming and pore formation, so that the zinc ferrite particles are evenly distributed inside the geopolymer carrier, so that the adsorption of the porous geopolymer loaded with zinc ferrite desulfurizer prepared by the present invention is enhanced, and at the same time, the residence time of H2S gas inside the geopolymer carrier is prolonged, thereby significantly improving the desulfurization effect of the zinc ferrite particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of a method for preparing a porous geopolymer-loaded zinc ferrite desulfurizer. DETAILED DESCRIPTION
[0031] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0032] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0033] Example 1
[0034] S1. Preparation of NaOH solution
[0035] Weigh an appropriate amount of granular or flake commercially available analytically pure NaOH (NaOH content ≥ 96%) and pour it into deionized water, stir until completely dissolved, and prepare a NaOH strong alkaline solution with a concentration of 12 mol / L. After sealing and cooling for 24 hours, bottle it for later use;
[0036] S2. Adjust the water glass modulus
[0037] Weigh an appropriate amount of the NaOH strong alkali solution in step S1, pour it into a commercially available sodium water glass solution (water glass modulus is 3.25, water content is 64.18%), stir evenly, so that the water glass modulus of the newly prepared water glass solution is 1.2, and the water content is 64.50wt%, let it stand and cool to room temperature, and bottle it for later use;
[0038] S3, dry mixed solid particle powder material
[0039] Weigh 100 g of metakaolin and zinc ferrite respectively, pour the weighed metakaolin and zinc ferrite into a planetary mixer (FY-681 cement sand-adhesive mixer) and dry-mix at a low speed of 120 r / min for 3 minutes, mix thoroughly to obtain a mixed dry material, and set aside for later use;
[0040] S4. Preparation of semi-finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0041] Weigh 100g of the water glass solution prepared in step S2, add 0.5wt% of the aluminum powder weighed to the mixed dry material in step S3 to the prepared water glass solution, stir with a glass rod for 5 minutes, let stand for 3 minutes, pour into a planetary mixer (FY-681 cement sand glue mixer) and stir with the mixed dry material in step S3 at a low speed of 120r / min for 3 minutes, then stir at a high speed of 280r / min for 3 minutes, and finally prepare a geopolymer carrier with a water-binder ratio of 0.38, a geopolymer-loaded zinc ferrite desulfurizer semi-finished slurry in the form of zinc ferrite, let stand at room temperature for 90 minutes for foaming, and set aside;
[0042] S5. Preparation of finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0043] The foamed semi-finished slurry in step S4 is poured into a mold, and placed in a programmable constant temperature and humidity test box at a temperature of 80° C. and a humidity of 60% for curing for 3 hours. Finally, the cured sample is crushed to obtain a finished product of a small-particle porous geopolymer-loaded zinc ferrite desulfurizer.
[0044] Example 2
[0045] S1. Preparation of NaOH solution
[0046] Weigh an appropriate amount of granular or flake commercially available analytically pure NaOH (NaOH content ≥ 96%) and pour it into deionized water, stir until completely dissolved, and prepare a NaOH strong alkaline solution with a concentration of 10 mol / L. After sealing and cooling for 24 hours, bottle it for later use;
[0047] S2. Adjust the water glass modulus
[0048] Weigh an appropriate amount of the NaOH strong alkali solution in step S1, pour it into a commercially available sodium water glass solution (water glass modulus is 3.25, water content is 64.18%), stir evenly, so that the water glass modulus of the newly prepared water glass solution is 1.8, and the water content is 66.78wt%, let it stand and cool to room temperature, and bottle it for later use;
[0049] S3, dry mixed solid particle powder material
[0050] Weigh 100 g of metakaolin and zinc ferrite respectively, pour the weighed metakaolin and zinc ferrite into a planetary mixer (FY-681 cement sand-adhesive mixer) and dry-mix at a low speed of 145 r / min for 10 minutes, mix thoroughly to obtain a mixed dry material, and set aside for later use;
[0051] S4. Preparation of semi-finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0052] Weigh 100g of the water glass solution prepared in step S2, add 1.0wt% of zinc powder weighed to the mixed dry material in step S3 to the prepared water glass solution, stir with a glass rod for 5 minutes, let stand for 5 minutes, pour into a planetary mixer (FY-681 cement sand glue mixer) and stir with the mixed dry material in step S3 at a low speed of 160r / min for 5 minutes, then stir at a high speed of 250r / min for 5 minutes, and finally prepare a geopolymer carrier with a water-binder ratio of 0.45, a geopolymer-loaded zinc ferrite desulfurizer semi-finished slurry in the form of zinc ferrite, let stand at room temperature for 90 minutes for foaming, and set aside;
[0053] S5. Preparation of finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0054] The foamed semi-finished slurry in step S4 is poured into a mold, and placed in a programmable constant temperature and humidity test box at a temperature of 80° C. and a humidity of 60% for curing for 3 hours. Finally, the cured sample is crushed to obtain a finished product of a small-particle porous geopolymer-loaded zinc ferrite desulfurizer.
[0055] Example 3
[0056] S1. Preparation of NaOH solution
[0057] Weigh an appropriate amount of granular or flake commercially available analytically pure NaOH (NaOH content ≥ 96%) and pour it into deionized water, stir until completely dissolved, and prepare a NaOH strong alkaline solution with a concentration of 12 mol / L. After sealing and cooling for 24 hours, bottle it for later use;
[0058] S2. Adjust the water glass modulus
[0059] Weigh an appropriate amount of the NaOH strong alkali solution in step S1, pour it into a commercially available sodium water glass solution (water glass modulus is 3.25, water content is 64.18%), stir evenly, so that the water glass modulus of the newly prepared water glass solution is 1.2, and the water content is 64.50wt%, let it stand and cool to room temperature, and bottle it for later use;
[0060] S3, dry mixed solid particle powder material
[0061] Weigh 60 g of metakaolin and 100 g of zinc ferrite, pour the weighed metakaolin and zinc ferrite into a planetary mixer (FY-681 cement sand-adhesive mixer), dry mix at a low speed of 145 r / min for 10 minutes, mix thoroughly to obtain a mixed dry material, and set aside for later use;
[0062] S4. Preparation of semi-finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0063] Weigh 100g of the water glass solution prepared in step S2, add 0.5wt% of the aluminum powder weighed to the mixed dry material in step S3 to the prepared water glass solution, stir with a glass rod for 5 minutes, let stand for 3 minutes, pour into a planetary mixer (FY-681 cement sand glue mixer) and stir with the mixed dry material in step S3 at a low speed of 145r / min for 3 minutes, and then stir at a high speed of 280r / min for 3 minutes, and finally prepare a geopolymer carrier with a water-binder ratio of 0.38, a geopolymer-loaded zinc ferrite desulfurizer semi-finished slurry in the form of zinc ferrite, let stand at room temperature for 90 minutes for foaming, and set aside;
[0064] S5. Preparation of finished product of porous geopolymer-supported zinc ferrite desulfurizer
[0065] The foamed semi-finished slurry in step S4 is poured into a mold, and placed in a programmable constant temperature and humidity test box at a temperature of 80° C. and a humidity of 60% for curing for 3 hours. Finally, the cured sample is crushed to obtain a finished product of a small-particle porous geopolymer-loaded zinc ferrite desulfurizer.
[0066] Example 4
[0067] Except that the aluminum powder in step S4 is replaced by zinc powder, the contents of the remaining steps are the same as those in Example 3.
[0068] Example 5
[0069] Except that 60 g of metakaolin in step S3 is replaced by 40 g of metakaolin, the contents of the remaining steps are the same as those in Example 1.
[0070] Example 6
[0071] Except that the aluminum powder in step S4 is replaced by zinc powder, the contents of the remaining steps are the same as those in Example 5.
[0072] The porous geopolymer-loaded zinc ferrite desulfurizer prepared in the above Examples 1-6 all have stable structures, certain strength, are not easy to crush, and the zinc ferrite solid particles are evenly distributed, and the desulfurization effect is good.
[0073] Test Example 1
[0074] The porous geopolymer prepared in the above Examples 1-6 was used to load the zinc ferrite desulfurizer to carry out a desulfurization test, and the specific steps are as follows:
[0075] S1. Preparation of sulfur-containing solution
[0076] Weigh an appropriate amount of sulfur-containing compound, pour it into water, stir until completely dissolved, prepare a sulfur-containing solution (the initial concentration of sulfur in the solution is 300 mg / g), seal it, and bottle it for later use.
[0077] S2. Adsorption desulfurization using porous geopolymer loaded with zinc ferrite desulfurizer
[0078] 60g of the crushed porous geopolymer-supported zinc ferrite desulfurization adsorbent prepared in Examples 1-6 were weighed and placed in 6 250ml conical flasks, and 100ml of the sulfur-containing solution prepared in step S1 was added at the same time. The flasks were placed in a constant temperature (20°C) oscillator (speed 160-260r / min), and samples were taken after 10 minutes to record the corresponding adsorption solubility, and the adsorption amount of sulfur by the adsorbent was calculated.
[0079] The sulfur desorption amount of the porous geopolymer-supported zinc ferrite desulfurizer is shown in Table 1. It can be seen from Table 1 that the desulfurization effect of the porous oligomer-supported zinc ferrite desulfurizer increases with time, but the desulfurization amount begins to slow down in the later period, which is because the adsorbent has gradually reached saturation.
[0080] Table 1 Desorption of sulfur by porous geopolymer supported zinc ferrite desulfurizer in Examples 1-6
[0081]
[0082] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a porous geopolymer-supported zinc ferrite desulfurizer, characterized in that: The steps include: S1. Preparation of NaOH solution Weigh an appropriate amount of granular or flake NaOH and pour it into water, stir until completely dissolved to prepare a NaOH strong alkaline solution, seal it and let it stand and cool for 24 hours, then bottle it for later use; S2. Adjust the water glass modulus Weigh an appropriate amount of the NaOH strong base solution in step S1, pour it into a commercially available sodium water glass solution, let it stand and cool, obtain the prepared water glass solution, and bottle it for later use; The water glass modulus of the prepared water glass solution is between 1.2 and 2.0; the water glass modulus of the commercially available sodium water glass solution is 3.25, and the water content is 64.18%; S3, dry mixed solid particle powder material Weigh appropriate amounts of metakaolin and zinc ferrite, pour the two substances into a blender and dry mix them, mix thoroughly to obtain a mixed dry material, and set aside for later use; The mass ratio of metakaolin to zinc ferrite is 0.2-1.0:1; S4. Preparation of semi-finished product of porous geopolymer-supported zinc ferrite desulfurizer Weigh an appropriate amount of aluminum powder or zinc powder and add it to the prepared water glass solution in step S2, stir it with a glass rod for 3-5 minutes, let it stand for 3-5 minutes, pour it into a mixer and stir it together with the mixed dry material in step S3 for 6-10 minutes, and finally obtain a semi-finished slurry of a geopolymer-loaded zinc ferrite desulfurizer in the form of a geopolymer carrier-loaded zinc ferrite, let it stand for foaming and then set aside; The water-to-binder ratio of the geopolymer carrier is 0.38-0.5; The mass of the aluminum powder or zinc powder is 0.5-1.0wt% of the mixed dry material in step S3; S5. Preparation of finished product of porous geopolymer-supported zinc ferrite desulfurizer The foamed semi-finished slurry in step S4 is poured into a mold, and placed in a programmable constant temperature and humidity test box for curing for 3-6 hours. Finally, the cured sample is crushed to obtain a finished product of a small-particle porous geopolymer-loaded zinc ferrite desulfurizer.
2. The method for preparing a porous geopolymer-supported zinc ferrite desulfurizer according to claim 1, characterized in that: The water in step S1 is deionized water, the purity of the granular or flaky NaOH is ≥96%, and the concentration of the NaOH strong alkaline solution is 8-12 mol / L.
3. The method for preparing a porous geopolymer-supported zinc ferrite desulfurizer according to claim 1, characterized in that: The mixer in step S3 and step S4 is a planetary mixer, and the dry mixing in step S3 specifically refers to low-speed mixing at a rotation speed of 120-180 r / min for 5-10 minutes.
4. The method for preparing a porous geopolymer-supported zinc ferrite desulfurizer according to claim 1, characterized in that: The stirring for 6-10 minutes in step S4 specifically refers to first stirring at a low speed of 120-180 r / min for 3-5 minutes, and then stirring at a high speed of 200-300 r / min for 3-5 minutes.
5. The method for preparing a porous geopolymer-supported zinc ferrite desulfurizer according to claim 1, characterized in that: The foaming time in step S4 is not less than 90 minutes.
6. The method for preparing a porous geopolymer-supported zinc ferrite desulfurizer according to claim 1, characterized in that: The curing temperature of the programmable constant temperature and humidity test box in step S5 is 40-80° C., and the humidity is 50-80%.
Citation Information
Patent Citations
Anti-pulverization medium-high temperature coal gas zinc ferrite desulfurizer and preparation thereof
CN101440313A
Method for preparing geopolymer adsorption material by using Bayer process red mud
CN103920457A